Site-Specific Ground Response Analysis using the Geotechnical Dataset in Moderate Seismicity Region - Imtiyaz Akbar, Najar; Raudhah, Ahmadi; Mohd. Azizul Hafiz, Jamian; Hasmida, Hamza; Azrin, Ahmad; Sin, Chin Hon (NAUN Publication, 2022)
An understanding of the soil response to dynamic waves from the earthquakes is an important aspect of engineering safety measures against tremors. This research presents the equivalent linear site response analysis of the Miri district by using a geotechnical dataset. The main objective of this paper is to study the amplification factor for the district of Miri. Analysis of site response is critical in determining the earthquake risk and harm allocation during earthquakes. The standard penetration test ‘N’ value (SPT-N) has been used in this study. A specific soil-type relationship has been used between shear wave velocity and SPT-N value to produce profiles of shear wave velocity in each borehole site in the Miri district. For all SPT-N borehole sites, site response parameters were interpolated to produce site response maps and shear wave velocity maps in the geographical information system (GIS) environment. The research showed that the Malaysian national annex to Eurocode 8 (MNA-EC8) site class C, D and E are dominant in the Miri district. Due to the inadequacy of records of input ground motions of low-to-moderate seismicity regions, this research used an earthquake record from other locations well-matched from a target response spectrum with similar characteristics obtained from the Pacific Earthquake Engineering Research Center (PEER) online database (PEER NGA). The equivalent linear method (EQL) using DEEPSOIL is an extensively researched numeric technique that is used for assessment of site response. From the results, it has been found that the amplification ratio varies from 2.1 to 4.79 and it suggests that it is vital to study the site effect in the seismic hazard assessment of the Miri district. The work also emphasizes the relationship between seismic microzonation and site response analysis in order to reduce the adverse effects of earthquakes in Miri city by planning a proper land use.